2007
DOI: 10.1016/j.brainres.2007.05.026
|View full text |Cite
|
Sign up to set email alerts
|

A high soy diet enhances neurotropin receptor and Bcl-XL gene expression in the brains of ovariectomized female rats

Abstract: Estrogen is a powerful neuroprotective agent with the ability to induce trophic and antiapoptotic genes. However, concerns about negative overall health consequences of estrogen replacement after menopause have led to the adoption of other strategies to obtain estrogen's benefits in the brain, including the use of selective estrogen receptor modulators, high soy diets, or isoflavone supplements. This study sought to determine the ability of a high soy diet to induce neuroprotective gene expression in the femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 89 publications
1
12
0
Order By: Relevance
“…Recent data from our laboratory (Schreihofer et al 2005; Lovekamp-Swan et al 2007; Lovekamp-Swan et al 2007) and others (Setchell 2001; Lephart et al 2004; Burguete et al 2006) show a beneficial effect of a HS diet on the rodent brain. In particular, HS diets protect the brain from experimental ischemia and reduce apoptosis in the ischemic cortex (Schreihofer et al 2005; Burguete et al 2006; Lovekamp-Swan et al 2007).…”
Section: Introductionmentioning
confidence: 70%
“…Recent data from our laboratory (Schreihofer et al 2005; Lovekamp-Swan et al 2007; Lovekamp-Swan et al 2007) and others (Setchell 2001; Lephart et al 2004; Burguete et al 2006) show a beneficial effect of a HS diet on the rodent brain. In particular, HS diets protect the brain from experimental ischemia and reduce apoptosis in the ischemic cortex (Schreihofer et al 2005; Burguete et al 2006; Lovekamp-Swan et al 2007).…”
Section: Introductionmentioning
confidence: 70%
“…An estimated 30 -50% of humans produce 4=, 7 isoflavandiol (equol) from gut microflora, but genistein and daidzein remain the primary circulating isoflavones even in equol producers (7, 30). In contrast, the daidzein metabolite equol (4=, 7 isoflavandiol) is the primary circulating isoflavone in rodents consuming soy diets and accounts for ϳ80% of plasma isoflavones (24,28,29). Genistein, daidzein, and equol all act as phytoestrogens with preferential affinity for estrogen receptor ␤ (ER␤) over ER␣ (21, 36), but equol is more potent than genistein or daidzein on ER␣ (21, 36).…”
mentioning
confidence: 92%
“…A number of studies suggest that estrogen can alter the expression of neurotrophin receptors and perhaps even neurotrophins (16,17,35). We first demonstrated that estrogen enhances the expression of p75NTR in 22Rv1 prostate cancer cells, This effect occurs in association with the up-regulated expression of ESR2, suggesting that estrogen might not only directly regulate p75NTR expression, but may also influence the neurotrophin pathways via their receptors.…”
Section: Discussionmentioning
confidence: 87%